Early hypocalcemia following thyroidectomy in Kurmitola General Hospital, Dhaka, Bangladesh - Ali, Rahmot; Fatema, Kanij; Rahman, Mohammad Abdur; Mohammod, Maruf; Islam, M. Ashraful; Hasan, Mahmudul; Haque, M. Anwarul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Hypocalcaemia is a recognized complication after thyroidectomy, which may be transient or permanent due to impairment of blood supply, injury, or inadvertent removal of the parathyroid gland. Parathormone, secreted by parathyroid gland, plays an important role in calcium homeostasis. Purpose of this study was to enable early detection of hypocalcaemia after thyroidectomy, aiding in patient management, early discharge, and reduced hospital stay. Methods: This study was conducted in the otolaryngology and head-neck surgery department of Kurmitola General Hospital over 12 months, from January 2020 to December 2020. Patients with various indications were selected based on eligibility criteria through convenience sampling. Data were collected using a data collection sheet, then cleaned, edited, and tabulated. The results were analyzed using the student’s unpaired t-test (quantitative data) to determine their significance, with a p cut-off set at <0.05. Results: Data analysis of 30 patients (30% male, 70% female) revealed that 13 patients experienced hypocalcaemia, while 17 showed normocalcaemia. Among the 13 hypocalcaemic patients, 10 (76.92%) had asymptomatic (subclinical) hypocalcaemia, and 3 (23.08%) had symptomatic hypocalcaemia. Hypocalcaemia was observed in 46.15% of patients within 24 hours post-surgery, 38.46% within 48 hours, and 15.39% within 72 hours. The results indicated a female predominance in the development of hypocalcaemia. Conclusions: The study suggests that serum calcium levels significantly decrease after total thyroidectomy, with most cases occurring within 48-72 hours post-surgery.